The Effect of Iron Addition on the Magnetic Properties of Nano Particles Made from Cerium-Cobalt Composition by the Co-Precipitation Method - SJ Hosseini (Journal of Global Pharma Technology, 2017)
We have produced nanoparticles made fromco-precipitation-induced cerium-cobalt composition with 4:1 ratio. The results of the curve VSM represent the weak ferromagnetic properties of this compound at room temperature. But VSM curve shows an increase in ferromagnetism in this compound by eliminating (removing) the amount of oxygen, the mixture at 300 ° C under pressure of an atmosphere from H2 gas. In this compound, this property can be attributed to new created phases such as Co with hexagonal structure and properties of super paramagnetic and so can be due to the presence of Ce with Cubic structure in its ferromagnetic phase. By adding iron to the compound and production of new nanoparticles, XRD spectra shows that in addition to not changing the previous phases and with Cubic structures, two new phases and have been created with the same Cubic structure. The results of VSM curve represent the enhancement of ferromagnetism property of these nanoparticles which is caused by the presence of two new phases of iron and cobalt ferrite.